Knowledge and Behavior of Household Medicine Storage: A Study from the Urban area of Jakarta, Indonesia - Suci Ahda Novitri; Ofa Suzanti Betha; Annisa Triana Yusman; Mochamad Iqbal Nurmansyah; Estu Mahanani Dhilasari; Rurynta Ferly Shavira (YCAB Publisher, 2024)
Background: Medicine storage in households is significantly increasing due to the prevalence of self-medication behavior. Several people are still unfamiliar with proper medication storage procedures, which can affect the stability and effectiveness of the medicine. Objective: This study aimed to determine the knowledge and behavior of urban households regarding medicine storage in Jakarta. Methods: An analytical approach was used with the cross-sectional method and the data were collected through face-to-face interviews and observation. A total of 329 respondents and 1686 medicines were obtained through the purposive sampling method and the data collected were analyzed using univariate and bivariate analyses with SPSS 26. Results: The results showed that the majority of people have low knowledge (56.53%) and inappropriate behavior (57.45%), while most of the respondents got their medicines from a pharmacy or drugstore. The most commonly stored therapeutic classes were cough and cold medicines, including analgesic-antipyretics. A significant relationship was observed between age group and level of knowledge, as well as education, knowledge, and behavior related to the storage of medicine in households (p-value <0,05). Conclusion: In conclusion, the urban community in Jakarta has poor knowledge and inappropriate behavior regarding medicines storage in households, indicating the need for continuous education to promote proper practice. Keywords: Medicine storage; knowledge; behavior; households